Utility of world heart federation and modified World Health Organization echocardiographic diagnostic criteria of subclinical rheumatic heart disease in children of Manipur, India - Thangjam, Rajendra Singh; ., Rothangpui; Irom, Anil; Th, Rameshchandra; Ramakrishnan, Sivasubramanian; Saxena, Anita (International Journal of Advances in Medicine, 2019)
Background: A comparative prevalence studies using modified WHO and more stringent criteria of WHF2012 have not been conducted in this part of the country and so authors felt necessary to conduct such study in this North-eastern state of India. Methods: In this cross-sectional study, 3600 children aged 5-15 years (11.07±2.86, 51.90% male) from randomly selected schools of Manipur were examined clinically and by 2D colour doppler echocardiography. Results: Only one case of Clinical RHD with a combination of MR and AS was found, (prevalence of 0.28/1000) [CI: 0.04-1.97). Echocardiography detected 3 cases of definite subclinical (prevalence rate of 0.83/1000 (CI: 0.27-2.58], 14 cases of borderline subclinical RHD (prevalence rate of 3.9)/1000 (CI: 2.30-6.56) befitting WHF 2012 criteria, and 61 cases of borderline subclinical RHD befitting modified WHO criteria (prevalence rate of 16.9/1000)[ CI1.3-2.1].On follow up to 5 years, among the 3 cases with definite subclinical RHD, 2 had worsened and 1 remained non- progressive, while among the 14 subclinical borderline cases, 2 normalized, 6 remained non-progressive and 6 children were lost to follow up. Conclusions: Prevalence of RHD using echocardiography is several folds higher compared to clinical examination alone. While the number is reduced by about half using WHF criteria. However, the important of WHO criteria cannot simply be neglected, as all the subclinical cases by WHF criteria remains non-progressive, while one case of subclinical defined by WHO worsen on follow up.